Interaction between l-aspartate and the brucite [Mg(OH)2]–water interface. (15th April 2015) - Estrada, Charlene F.; Sverjensky, Dimitri A.; Pelletier, Manuel; Razafitianamaharavo, Angélina; Hazen, Robert M.
Abstract: The interaction of biomolecules at the mineral–water interface could have played a prominent role in the emergence of more complex organic species in life's origins. Serpentinite-hosted hydrothermal vents may have acted as a suitable environment for this process to occur, although little is known about biomolecule–mineral interactions in this system. We used batch adsorption experiments and surface complexation modeling to study the interaction ofl -aspartate onto a thermodynamically stable product of serpentinization, brucite [Mg(OH)2 ], over a wide range of initial aspartate concentrations at four ionic strengths governed by [Mg 2+ ] and [Ca 2+ ]. We observed that up to 1.0 μmol of aspartate adsorbed per m 2 of brucite at pH ∼ 10.2 and low Mg 2+ concentrations (0.7 × 10 −3  M), but surface adsorption decreased at high Mg 2+ concentrations (5.8 × 10 −3  M). At high Ca 2+ concentrations (4.0 × 10 −3  M), aspartate surface adsorption doubled (to 2.0 μmol m −2 ), with Ca 2+ adsorption at 29.6 μmol m −2 . We used the extended triple-layer model (ETLM) to construct a quantitative thermodynamic model of the adsorption data. We proposed three surface reactions involving the adsorption of aspartate (HAsp − ) and/or Ca 2+ onto brucite: 2 > SOH + H + + HAsp - → SOH 2 + > SAsp - + H 2 O, > SOH + HAsp - + Ca 2 + → SO - _ Ca ( HAsp ) + + H +, and > SOH + Ca 2 + + 2 H 2 O → SOH 2 + _ Ca ( OH ) 2 + H + . We used the ETLM to predict that brucite particle surface charge becomes more negative with increasing [Mg 2+ ], creating an unfavorable electrostatic environment for a negatively-charged aspartate molecule to adsorb. In contrast, our addition of Ca 2+ to the system resulted in Ca 2+ adsorption and development of positive surface charge. Our prediction of surface speciation of aspartate on brucite with Ca 2+ revealed that the calcium–aspartate complex is the predominant surface aspartate species, which suggests that the increase in aspartate adsorption with Ca 2+ is primarily driven by calcium adsorption. The cooperative effect of Ca 2+ and the inhibitive effect of Mg 2+ on aspartate adsorption onto brucite indicate that serpentinite-hosted hydrothermal fluids provide an ideal environment for these interactions to take place.